Exclusive Breastfeeding History Risk Factor Associated with Stunting of Children Aged 12–23 Months - Sari, Nurhalina; Manjorang, Marlida Yuliza; Zakiyah, Zakiyah; Randell, Madeleine (UI Scholars Hub, 2021)
Stunting (low height-for-age) remains a global and national health problem because it increases the risk of disturbances in growth and development and mortality. Banjar Margo District, Tulang Bawang Regency, has the second-highest prevalence in Lampung Province, Indonesia. This study aimed to analyze the association of exclusive breastfeeding history and stunting in children aged 12–23 months in Banjar Margo District. This study used a cross-sectional design on 193 children aged 12–23 months. It was primary data conducted between April and May 2018 with a questionnaire. Data analysis was performed using the chi-square test and multiple logistic regression. The result showed that of 193 children, 29.5% were stunted. Children who were not exclusively breastfed were 3.1 times (95%CI = 1.5–6.4) more at risk of stunting than those exclusively breastfed, after controlling for mothers with low education and unemployment factors as confounding variables. Health promotion activities in primary/integrated health care should be focused not only on mothers but also on other people involved in child care, such as grandparents, at-home caregivers, and day carers.